IPSis Outstanding Award Recipient: student recruitment of the year 2020 award - UiTM, IPSis (Institut Pengajian Siswazah (IPSis, 2021)
Institute of Graduate Studies (IGS) UiTM established an integrated marketing approach which includes key strategies, from aggressive student recruitment to increasing the visibility of UiTM postgraduate programmes. Each key activity was well-thought-out, focused on ongoing marketing campaigns instead of flash-in-the pan expensive advertisements. Most importantly, to capture the attention of potential postgraduate students, we aligned a social marketing approach with a theme that is relevant to people's lives, interests and selling experiences over products. What makes our approach a success was the way we combined both traditional and digital marketing to enhance an organic performance. We participated in traditional physical education campaigns in many targeted countries, such as Indonesia, Maldives, Sri Lanka, China and the Middle East and we initiated strong connections with universities and government of each country we visited. A partnership with these governments was intended to ensure trust of the government towards UiTM, as well as promoting UiTM as a place of study for the civil servants. The University to University (U2U) initiatives was promoted to establish close partnership between UiTM and universities overseas. Among the government that we have close ties is Indonesia, where the secretary-general of the United Development Party, is a PhD candidate in UiTM.